Morphological and multifractal studies of nanocrystalline Au films - Mehrdad Ahmadi; Maryam Nasehnejad (Progress in Physics of Applied Materials)
In this study, we investigated the surface morphology of Au coatings using atomic force microscopy (AFM). we aimed to understand the growth mechanisms and control the nano- and micro-structure of the films to achieve desired morphological properties. The study focused on films formed by the electrodeposition technique and examined the morphology evolution as a function of film thickness. To verify the crystalline structure of the films, X-ray diffraction (XRD) technique was employed. Statistical tests were conducted to confirm that the gold thin film surfaces under investigation exhibited multifractal properties. It is found that as the film thickness increased, the multifractality of the films became more pronounced, and the nonuniformity of the height probabilities also increased. Furthermore, it was observed that surfaces with greater roughness displayed larger nonlinearity and wider width of the multifractal spectrum. The results indicated that the multifractal spectrum had a right-hook shape, distinguishing between different film thicknesses even in small sizes of hundreds of nanometers. Overall, this study provides important insights into the surface morphology of Au coatings and highlights the significance of controlling growth mechanisms for fabricating flat Au films with desired morphological properties. These findings have implications for various applications in biological, electronic, and optical devices.